Association between demographic factors and side effects associated with COVID 19 vaccination - Shumyle, Dur E; Abdullah, Syed Muhammad; Sheikh, Hina Rafiq; Huda, Noor Ul; Shakoor, Asma; Butt, Hira (Infectious Diseases Journal of Pakistan, 2024)
Background: COVID vaccines were crucial in tackling the COVID 19 pandemic. However, they were also associated with side effects in the vaccinated population. These side effects included mild symptoms of COVID, fever, pain and swelling at the injection site. Hence, we evaluated the association between demographic factors and side effects in individuals following COVID vaccination. Material and methods: A cross- sectional study was conducted in 93 participants for a period of 1 year, from January 2022 to January 2023. This was a retrospective study in which information regarding the side effects of two COVID vaccines was collected from the participants post-vaccination. Demographic data of vaccinated individuals and side effects associated with COVID vaccination were documented on a standardized proforma. Statistical analysis was performed to ascertain any association between the demographic variables and vaccination-associated side effects. Results: Total 93 participants were evaluated during the study period. Our findings revealed higher frequency of vaccination-associated side effects in females and individuals above 20 years of age. The most common side effects included mild symptoms of COVID, fatigue and tiredness, fever, pain and swelling at the injection site and allergic reaction. None of these associations were found to be statistically significant. Conclusion: Our findings suggested relatively higher frequency of vaccination-associated side effects in females and in individuals above 20 years of age which according to our inference, might be attributable to certain immune mechanisms in the affected population. In order to develop effective and safer vaccines, we recommend multi-center studies to explore the immunogenesis of such side effects. Keywords: COVID, Demographics, Immunization, Vaccination-associated side effects